2009
DOI: 10.1016/j.bcp.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of molecular regulation of CCL3 induced calcium flux in monocytic cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 32A c c e p t e d M a n u s c r i p t 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…1F). These findings are consistent with the identification of functional ryanodine receptors in monocytes by others (Bracci et al, 2007;Cardaba and Mueller, 2009;Guidarelli et al, 2009 Scavenging extracellular ATP/ADP using apyrase severely attenuates Ca 2+ responses evoked by GPN (Fig. 3).…”
Section: Interaction Between Lysosomal and Er Ca 2+ Stores In Monocytessupporting
confidence: 91%
“…1F). These findings are consistent with the identification of functional ryanodine receptors in monocytes by others (Bracci et al, 2007;Cardaba and Mueller, 2009;Guidarelli et al, 2009 Scavenging extracellular ATP/ADP using apyrase severely attenuates Ca 2+ responses evoked by GPN (Fig. 3).…”
Section: Interaction Between Lysosomal and Er Ca 2+ Stores In Monocytessupporting
confidence: 91%
“…MCF-7 cells were harvested and treated as described previously [29]. Cells were loaded with Fura-2 as described previously [30,31]. Inhibitors were present during the 30 mins incubation period.…”
Section: Analysis Of Intracellular Calcium Ion Concentrationmentioning
confidence: 99%
“…It is well known that intracellular calcium plays a key role in PKC activation. Studies showed that release of intracellular calcium was prevented by simvastatin treatment in some cells (Cardaba and Mueller, 2009), which raised the possibility to target calcium as a regulatory signal. Alternatively, inhibition of HMG-CoA reductase may reduce mevalonate and its downstream metabolites which have shown significant influence in many intracellular processes.…”
Section: Discussionmentioning
confidence: 99%